Optimizing Plotagon Application as an IT-based Arabic Learning Media at MAN 1 Lamongan - Nur Aqilah Lutfiyah Rahma Opier; Syafi Syafi (Faculty of Education and Teacher Training, 2024)
This research aims to explore the use of Plotagon Story application as an information technology-based teaching tool to improve Arabic listening and speaking skills. The background of this research focuses on the importance of interactive learning tools to support student engagement, especially in the context of learning Arabic at MAN 1 Lamongan. The research uses a mixed method with quantitative and qualitative descriptive experimental design. The research sample consisted of (35) tenth grade students who were selected purposively. Data were collected through pre-test, post-test, observation, interviews, and documentation. The results of the research showed a significant increase in students' abilities in listening and speaking skills after using the Plotagon Story application, with the average post-test score of 84.17 compared to 61.37 in the pre-test. The N-Gain test showed an average gain of 0.61, indicating the effectiveness of the application in the